Survival and Isolation of Avian Mycoplasmas from Drinking Water of Infected Chickens. - Majid, M. Shah (1988)
Mycoplasma was inoculated into the drinking water of chicken and sampled at different time intervals. At a higher concentration, the organisms could be recovered from the water 24 hours post inoculation. Mycoplasma could not be recovered from the drinking water of infected chickens.